Factors affecting agricultural productivity in Doba woreda, Oromia national regional state, Ethiopia - Gizaw, Getaye (Archives of Business Research, 2020)
This Research was conducted to examine the determinant of agricultural productivity in Doba woreda. The objective of the study was to identify the major determinants of agricultural productivity in the study area. In order to achieve this objective, the study used both primary and secondary source of data. The primary data was collected through questionnaires and interviews. The secondary data was collected from agricultural office of the woreda and from other documents. The sampling technique was random sampling method with sample size of 100 respondents. The collected data was analyzed and interpreted using descriptive statistics. The majority farmers of the woreda live with large family size, small and fragmented land, large number of illiteracies, use traditional method of farming, and low female participation in the agricultural activities which lead agricultural productivity low. To avoid such problems, the woreda administration should be provide subsidy, credit with low interest rate, give training to illiterate to the farmers and also appreciate to use irrigation to avoid rainfall uncertainty.